(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2018)
A rapid, accurate, precise, stability indicating and enantioselective chiral HPLC method was developed and validated for the quantitative (S)- and (R)- omeprazole in omeprazole formulations along with determination of enantiomeric purity of (S)- omeprazole in esomeprazole formulations according to the guidelines of the United States of Pharmacopeia (USP) and International Conference on Harmonization (ICH). The chromatographic separation was achieved with n-hexane/ 2-propanol/ acetic acid/ triethylamine (100 : 20 : 0.2 : 0.1, v/v) at a flow rate of 1.2 ml/min on Chiralcel OD-H and detected at 300 nm. The method showed good linearity, high sensitivity with detection limit (LOD) of 0.71 and 1.16 μg/ml and quantitation limit (LOQ) of 2.16 and 3.51 μg/ml for (S)- and (R)- omeprazole, respectively. The average percentage of recovery was found to be 100.85% to 101.36% for (S)- and 99.81% to 101.62% for (R)- omeprazole. The average percentage of relative standard deviation (% RSD) for intra- and inter- day precision were found to be 0.05% and 0.19% for (S)- and 0.03% and 0.13% for (R)- omeprazole, respectively. Stability study was performed under stress conditions. Microthermal analysis of omeprazole was also performed by thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and scanning electron microscopy (SEM) to assess the physical and chemical behavior of the drug. The method was successfully applied to the quantitation of (S)- and (R)- omeprazole for omeprazole and as well as determination of (S)- omeprazole purity for esomeprazole formulations. Dhaka Univ. J. Pharm. Sci. 16(2): 221-233, 2017 (December)